The Effect Of The Implementation Of Corporate Social Responsibility Good Corporate Governance And Tri Hita Karana On The Financial Performance Of Village Credit Institutions (Lpd) Throughout Tabanan District - I Kt Puja Wirya SANJAYA; I.B Made Putra MANUABA; L.G.P Sri Eka JAYANTI (Journal of Tourism Economics and Policy, 2022)
The Village Credit Institution (LPD), a financial institution that carries out community fund collection and distribution activities, operates in an administrative area of The Customary Village based on the kinship between villagers in Bali. Bali Provincial Regulation Number 8, 2002 concerning LPD, which requires LPD to divide its profit 20% for village development and 5% for social funds, reflects the social obligations that must be applied by LPD, which in accounting is known as Corporate Social Responsibility (CSR), in addition, LPD uses loans from Regional Development Banks. Therefore, the principles of good corporate governance must be applied by LPD to reduce conflicts of interest between LPD managers as agents and owners, namely villages and between LPD managers and creditors, namely the Bali Regional Development Bank and maintain good relations and ensure the fullness of the rights of parties interested in the functions and objectives of the LPD itself. Tri Hita Karana culture is a local Balinese wisdom used as an individual foundation in every activity, especially in indigenous village communities with lpd owners